2008
DOI: 10.1007/s11103-008-9440-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity to oxidative stress in transgenic tobacco plants with decreased glutathione reductase activity leads to a decrease in ascorbate pool and ascorbate redox state

Abstract: To investigate the possible mechanisms of glutathione reductase (GR) in protecting against oxidative stress, we obtained transgenic tobacco (Nicotiana tabacum) plants with 30-70% decreased GR activity by using a gene encoding tobacco chloroplastic GR for the RNAi construct. We investigated the responses of wild type and transgenic plants to oxidative stress induced by application of methyl viologen in vivo. Analyses of CO(2) assimilation, maximal efficiency of photosystem II photochemistry, leaf bleaching, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 65 publications
5
46
0
Order By: Relevance
“…In Arabidopsis, chloroplast and mitochondrial dual-targeted GR2 knockout caused lethality in embryos (Tzafrir et al 2004). As well, chloroplastic GR knocked-down tobacco (Ding et al 2009) and tomato (Shu et al 2011) showed susceptibility to MV and chilling, respectively. These results indicate that chloroplast or mitochondrial GR plays a key role in stress tolerance and plant development.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In Arabidopsis, chloroplast and mitochondrial dual-targeted GR2 knockout caused lethality in embryos (Tzafrir et al 2004). As well, chloroplastic GR knocked-down tobacco (Ding et al 2009) and tomato (Shu et al 2011) showed susceptibility to MV and chilling, respectively. These results indicate that chloroplast or mitochondrial GR plays a key role in stress tolerance and plant development.…”
Section: Discussionmentioning
confidence: 93%
“…Altered chloroplastic GR affects the glutathione redox state and pool size. For example, reduced expression of chloroplastic GR led to decreased GSH content and GSH/GSSG ratio in tobacco (Ding et al 2009) and tomato (Shu et al 2011) after MV and chilling treatment, respectively. Conversely, overexpression Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pea, cytosolic GR has been well characterized at the biochemical level (Edwards et al, 1990;Stevens et al, 2000), but the functional significance of the enzyme remains unclear. Underexpression or overexpression studies in tobacco and poplar (Populus species) have reported significant effects of modifying chloroplast GR capacity (Aono et al, 1993;Broadbent et al, 1995;Foyer et al, 1995;Ding et al, 2009). Less evidence is available supporting an important role for cytosolic GR.…”
mentioning
confidence: 99%